Fractional Order Dynamical Behavior of Dengue Hemorrhagic Fever with Saturation Factor (Journal of Nonlinear Modeling and Analysis, 2025)
In this study, we propose a modified fractional order derivative inthe scope of Caputo to investigate the dynamics of Dengue fever transmission.The existence, uniqueness and boundedness of the fractional model were established using a fixed-point approach. The stability analysis of the model wasdone with respect to the reproduction number which was found to be stablelocally and globally at infection free and endemic state respectively. The fractional order (DHF) model was estimated using the fractional Adams-Bashforthpredictor-corrector technique. Additionally, the numerical validation was doneto ascertain the impact of various parameters on the dynamics as a whole, aswell as the effect of vaccines on the model. The graphical solutions show thatthe fractional order $(α)$ and vaccinations affect the dynamics of the modelwhen they are varied within the model. The findings indicate that saturation of infectious individuals in the system helps to flatten out the infectiontransmission.